A direct and fully general implementation of influence lines/surfaces in finite element software. (June 2018) - Jepsen, Michael S.; Damkilde, Lars
Highlights: Direct method for computation of influence lines/surfaces in any FE program. The method identifies an influence function by a single load case of consistent forces. The method is general and can be applied for all structural finite elements. Abstract: In the paper a general and direct method for implementation of influence lines in finite element software is provided. Generally influence lines are applied to identify the most critical location and combination of live loads in civil engineering structures. The proposed method is based on the Müller-Breslau principle and the basic idea is to equate discontinuous displacement fields with consistent nodal forces, thus obtaining influence functions only applying a single load case without changing the geometry or boundary conditions of the finite element model. Initially the method is developed by means of some illustrative beam problems, where the consistent nodal forces for angular, lateral and axial displacement discontinuities for a Bernoulli-Euler beam element are derived. Finally it is shown that the method is fully general and efficient in identifying the influence functions of generalized stresses in e.g. plates and shells.